Review of Andrew F. Jones. 2001. Yellow Music: Media Culture and Colonial Modernity in the Chinese Jazz Age. Durham, NC: Duke University Press - Wilson, Dale (Current Musicology, 2001)
Mimi zhi yin, meaning literally "decadent sounds," is a classical Chinese expression dating to the Han dynasty that is used to denote music that is both lewd and harmful. In the ancient Chinese context, sound was viewed as a potential register of the moral integrity of the state, as well as a power-ful tool to influence political stability and control. A reference to mimi zhi yin not only signified portentous or threatening sounds, but also served as a tacit reminder that sound is a power that may be harnessed for utilitarian ends.